Androgyyni vai moneus? : tulkintoja Edith Södergranin runosta 'Vierge moderne' - Helle, Anna (Naistutkimus, 2005)
Summary: Androgyne or multiplicity?.
Keywords: Södergran, Edith : Vierge moderne; runot; tulkinta; dikter; tolkning (kognition)